Graph Representation Comparative Study - Arman, Nabil (2005 International Conference on Foundations of Computer Science (FCS'05), 2005)
There are a number of graph representation schemes that have been used in graph algorithms. In this short article, a comparison is conducted among three major representations of directed graphs to illustrate the main advantages and disadvantages of each representation scheme. The reason for conducting this study is to show that one of the schemes is overlooked despite the fact that it has more information than the other schemes and this information is very useful in improving the performance of many graph algorithms.
Keywords: Graph Representation, Path Matrix Representation